2009
DOI: 10.1007/s11604-009-0345-0
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal practical measurement of skin color and moisture during and after breast-conserving therapy: influence of neoadjuvant systemic therapy

Abstract: Objective analysis is useful for detailed assessment of radiation dermatitis. NST did not worsen skin reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
27
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 12 publications
6
27
0
Order By: Relevance
“…This issue (optimal organ at risk for radiation dermatitis) could be left for further investigation. Actually, until now, larger breast has been identified as an important predictor of radiation dermatitis (8)(9)(10)(11)(12)(13)(14). Also, in this study, V5 (whole body) and V40 (skin volume) showed strong correlations to body mass index.…”
Section: Variablessupporting
confidence: 60%
See 2 more Smart Citations
“…This issue (optimal organ at risk for radiation dermatitis) could be left for further investigation. Actually, until now, larger breast has been identified as an important predictor of radiation dermatitis (8)(9)(10)(11)(12)(13)(14). Also, in this study, V5 (whole body) and V40 (skin volume) showed strong correlations to body mass index.…”
Section: Variablessupporting
confidence: 60%
“…Several influential factors have been reported for radiation dermatitis. Larger breast volume, lower radiotherapy energy, larger irradiated volume, boost irradiation, and absence of skin care elevated severe radiation dermatitis (8)(9)(10)(11)(12)(13)(14). Inhomogeneity of radiation dose distribution also caused severe radiation dermatitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pre-WBRT WC ratio (WCR (0) = I 0 / N 0 , irradiated breast skin WC divided by contralateral breast WC) was calculated. Taking intra- and inter-individual variation ( 5 ) into account, RWCR ( t ) , (WCR normalized by pre-WBRT state) was then calculated using the following formula ( 11 ) where I 0 and I t correspond to WC on the irradiated breast at pre-WBRT and each study point, and N 0 and N t correspond to WC on the non-irradiated breast at pre-WBRT and each study point.…”
Section: Methodsmentioning
confidence: 99%
“…It measures the electrical capacitance of the skin surface as an indicator of stratum corneum hydration, which is dependent on the high dielectrical constant of WC relative to other skin components. The corneometer has been demonstrated to be useful for objectively assessing radiation induced skin reactions for breast cancer patients ( 11 ). Skin-related signs and symptoms were also assessed.…”
Section: Introductionmentioning
confidence: 99%